STATURE ESTIMATE OF CHILDREN WITH CEREBRAL PALSY THROUGH SEGMENTAL MEASURES: A SYSTEMATIC REVIEW - Joel Alves Lamounier; Nathália Macedo Marteletto; Cristina Amaral Calixto; Marcia Reimol de Andrade; Jacqueline Domingues Tibúrcio (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To review studies that evaluate the correspondence between the estimate height via segmental measures and the actual height of children with cerebral palsy. Data sources: Systematic literature review between 1995-2018, guided by the PRISMA criteria (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), in PubMed, BVS, MEDLINE and Lilacs databases. The descriptors, connected by the AND Boolean Operators, were: anthropometry, cerebral palsy, child and body height. The research comprised papers in Portuguese, English and Spanish, with Qualis-CAPES equal or superior to B3 that addressed the question: "Is there any correlation between estimate height by equations and direct height measures in children with cerebral palsy?" 152 studies were recovered and seven were selected. Their methodological quality was assessed by the scale of the Agency for Healthcare Research and Quality (AHRQ). Data synthesis: Most studies showed no correspondence between estimated and real height. Studies that showed coincidence of the measures contain limitations that could jeopardize the results (sample losses, small samples and exclusion of patients with severe contractures, scoliosis and severe cerebral palsy). Japanese researchers developed an equation which harmoniously aligns the statures; the study comprised only Japanese patients, though. Conclusions: Given the importance of accuracy in height measures to evaluate infant health, it is crucial to carry out more researches in order to safely establish an association between both estimate and real statures. The development of anthropometric protocols, emerged from such researches, would benefit the follow-up of children with severe psychomotor disabilities.